2021-2022 Quick Reference Guide to Citrus Insecticides and Miticides - L. M. Diepenbrock; L. L. Stelinski; J. D. Burrow; J. A. Qureshi (EDIS, 2021)
A two-page quick reference guide to citrus insecticides and miticides recommended in the Florida Citrus Pest Management Guide, their effects on important citrus pests, and their natural enemies.